Day 3 Wed, June 27, 2018 2018
DOI: 10.2118/191275-ms
|View full text |Cite
|
Sign up to set email alerts
|

Calculating Asphaltenes Precipitation Onset Pressure by Using Cardanol as Precipitation Inhibitor: A Strategy to Increment the Oil Well Production

Abstract: Asphaltenes precipitation is considered a formation damage problem, which can reduce the oil recovery factor. It fouls piping and surface installations, as well as cause serious flow assurance complications and decline oil well production. Therefore, researchers have shown an interest in chemical treatments to control this phenomenon. The aim of this paper is to assess the asphaltenes precipitation onset of crude oils in the presence of cardanol, by titrating the crude with n-heptane. Moreover, based on this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The researchers investigated the effect on inhibiting the asphaltene deposition of cardanol. The results of this study showed that the asphaltene precipitation onsets (APO) of the crude oil were 2.06, 2.30, and 6.02 mL n-heptane/g of oil and cardanol was an effective inhibitor of asphaltene precipitation [26]. Ram et al investigated the effect of pressure-depletion-induced asphaltene precipitation on interfacial properties of live-oil, brine, and quartz systems as well as the hysteresis of the contact angle after aging in high pressure and high temperature (HPHT) conditions.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The researchers investigated the effect on inhibiting the asphaltene deposition of cardanol. The results of this study showed that the asphaltene precipitation onsets (APO) of the crude oil were 2.06, 2.30, and 6.02 mL n-heptane/g of oil and cardanol was an effective inhibitor of asphaltene precipitation [26]. Ram et al investigated the effect of pressure-depletion-induced asphaltene precipitation on interfacial properties of live-oil, brine, and quartz systems as well as the hysteresis of the contact angle after aging in high pressure and high temperature (HPHT) conditions.…”
Section: Introductionmentioning
confidence: 85%
“…CO 2 0.00 C 17 2.55 N 2 1.78 C 18 2.36 C 1 27.45 C 19 2.08 C 2 1.04 C 20 1.77 C 3 0.18 C 21 1.67 iC 4 0.06 C 22 1.53 nC 4 0.04 C 23 1.42 iC 5 0.00 C 24 1.31 nC 5 0.00 C 25 1.38 C 6 0.00 C 26 1.52 C 7 0.15 C 27 1.78 C 8 0.24 C 28 1.94 C 9 0.83 C 29 1.86 C 10 0.45 C 30 1.62 C 11 0.88 C 31 1.15 C 12 1.42 C 32 0.90 C 13 1.97 C 33 0.72 C 14 2.35 C 34 0.61 C 15 2.17 C 35 0.56 C 16 2.33 C 36+ 27.93 The composition of crude oil with different CO 2 and N 2 injection volumes was simulated by inputting the composition of crude oil into the PVTsim Nova. The molar volume content change of the light hydrocarbon components (C 1 -C 4 ) and the heavy hydrocarbon components (C 36+ ) induced by CO 2 and N 2 injection are shown in Table 3.…”
Section: Components Molar Volume Content (Mol %) Components Molar Volmentioning
confidence: 99%
“…The pressure at which this occurs, at a given temperature, is named precipitation onset pressure. Knowing this value accurately provides more tools for reservoir and production engineers to make decisions to propose alternatives and solutions to overcome the problem related to the destabilization of asphaltenes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Many works involving the determination of asphaltene precipitation at atmospheric pressure are available [15][16][17][18][19][20][21][22][23][24][25]. Some others investigate the behavior of asphaltenes at reservoir conditions [14,[26][27][28][29][30][31][32]. These inconveniences generate economic damage, as they can alter petrophysical properties causing severe damage to the reservoir; for example, the presence of asphaltenes in the solid form can lead to the blocking of pores in the production formation, a loss of effective porosity, changes in permeability, changes in wettability, and an increase in oil viscosity [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation